Challenges in pea breeding for tolerance to drought: Status and prospects - Bagheri, Maryam; Santos, Carla S.; Rubiales, Diego; Vasconcelos, Marta W. (Annals of applied biology, 2023)
Drought is increasingly frequent in the context of climate change and is considered a major constraint for crop yield. Water scarcity can impair growth, disturb plant water relations and reduce water use efficiency. Pea (Pisum sativum) is a temperate grain legume rich in protein, fibre, micronutrients and bioactive compounds that can benefit human health. In reducing pea yield because of drought, the intensity and duration of stress are critical. This review describes several drought resistance mechanisms in pea based on morphology, physiology and biochemical changes during/after the water deficit period. Drought tolerance of pea can be managed by adopting strategies such as screening, breeding and marker‐assisted selection. Therefore, various biotechnological approaches have led to the development of drought‐tolerant pea cultivars. Finally, the main objective of the current research is to point out some useful traits for drought tolerance in peas and also, mention the methods that can be useful for future studies and breeding programmes. Major knowledge gaps identified in pea breeding for drought tolerance, available tools to address these challenges and possible solutions that will enable the increase of genomic resources available for drought tolerant pea plants.